2011
DOI: 10.1016/j.jaut.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-1 is required for systemic self-tolerance in newly generated T cells during the establishment of immune homeostasis

Abstract: Lymphopenia driven T cell activation is associated with autoimmunity. That lymphopenia does not always lead to autoimmunity suggests that control mechanisms may exist. We assessed the importance of the co-inhibitory receptor programmed death-1 (PD-1) in the control of lymphopenia-driven autoimmunity in newly generated T cells vs. established peripheral T cells and in thymic selection. PD-1 was not required for negative selection in the thymus or for maintenance of self tolerance following transfer of establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 57 publications
2
84
0
2
Order By: Relevance
“…Given that most of these cells recognize self-ligands, although with low affinity (56), it is reasonable to think that they could have an autoreactive potential. In line with this hypothesis, Thangavelu et al (57), although not examining GzmB expression on T cells, have shown in a recent report that PD-1 KO recent thymic emigrants cause a lethal autoimmune-like disease in chronically lymphopenic hosts.…”
Section: Discussionmentioning
confidence: 86%
“…Given that most of these cells recognize self-ligands, although with low affinity (56), it is reasonable to think that they could have an autoreactive potential. In line with this hypothesis, Thangavelu et al (57), although not examining GzmB expression on T cells, have shown in a recent report that PD-1 KO recent thymic emigrants cause a lethal autoimmune-like disease in chronically lymphopenic hosts.…”
Section: Discussionmentioning
confidence: 86%
“…The PD-1 pathway is critical for both positive and negative selection of T cells in the thymus and is necessary for development of systemic selftolerance. [33][34][35][36] As such, previous PD-1 blockade could have longlasting effects on the thymus, resulting in altered PD-1 expression and imbalanced processing of the large number of T cells infused during HSCT. In addition, PD-1 blockade may alter posttransplant immune reconstitution through its effects on circulating cytokines and antigenpresenting cells.…”
Section: Absolute Cd4+ T Cellsmentioning
confidence: 99%
“…Absence of PD-1 is associated with development of a multi-organ autoimmunity after lymphopenia-induced proliferation (LIP) [61]. Interestingly, the disorder was only developed by mice that were treated with PD-1 -/-hematopoietic stem cells (HSC), and not by those reconstituted with mature PD-1 -/-lymphocytes, indicating that the PD-1 expression is critical to establish self-tolerance of the recentthymic emigrants [61].…”
Section: Accepted Manuscriptmentioning
confidence: 99%